2019
DOI: 10.47213/bp.v1i2.21
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Problem Based Learning terhadap Hasil Belajar Ipa Siswa Ditinjau dari Kemampuan Dasar Matematika

Abstract: Penelitian ini bertujuan untuk mengetahui apakah hasil belajar IPA bagi siswa yang belajar dengan pembelajaran problem based learning lebih tinggi daripada siswa yang belajar secara konvensional dan mengetahui siswa yang mempunyai kemampuan dasar matematika tinggi, lebih tinggi daripada siswa yang mempunyai kemampuan dasar matematika rendah. Rancangan penelitian ini adalah quasi experiment (eksperimen semu) desain faktorial 2 x 2. Variabel bebasnya adalah model pembelajaran dan kemampuan dasar matematika. Vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Other research findings also state that the results of this PBL interactive multimedia meet the criteria of validity in learning and practicality in learning (Khamzawi & Wiyono, 2015). Other findings also state significant differences in science learning outcomes between students who learn to follow the conventional learning model in fifth-grade elementary school (Kristiana & Radia, 2021;Lestari, 2019). So based on these findings, it can be concluded that interactive learning multimedia is proven to impact student learning outcomes positively.…”
Section: Introductionmentioning
confidence: 90%
“…Other research findings also state that the results of this PBL interactive multimedia meet the criteria of validity in learning and practicality in learning (Khamzawi & Wiyono, 2015). Other findings also state significant differences in science learning outcomes between students who learn to follow the conventional learning model in fifth-grade elementary school (Kristiana & Radia, 2021;Lestari, 2019). So based on these findings, it can be concluded that interactive learning multimedia is proven to impact student learning outcomes positively.…”
Section: Introductionmentioning
confidence: 90%